Leadership Professional Identity. Self-Perception of School Principals - López Yáñez, Julián; Sánchez-Moreno, Marita; Camarero Figuerola, Marta; Renta Davids, Ana Inés (Avances en Supervisión Educativa, 2024)
This paper examines the self-perception of school principals in Spain regarding their professional identity as educational leaders. The data were collected through a questionnaire designed by our research team, yielding a total of 779 valid responses. Data analysis identified three profiles of principals: committed, resilient, and transient, which were analysed according to: their motivation to be a school principal; satisfaction with their performance and some institutional aspects; and self-perception about their own capacities. Additionally, other issues regarding the construction of their professional identity were explored. The study’s findings highlight the need for institutional support for educational leaders, particularly during their transition from teaching roles. They also provide specific insights into the areas and approaches on which such support should be focused.